ANALISIS EFEKTIVITAS METODE WAFA DAN PEMBIASAAN TAHSIN TERHADAP PENINGKATAN KEMAMPUAN TAHFIDZUL QUR’AN SANTRI ORANG ASLI PAPUA (OAP) DI RUMAH QUR’AN FAKFAK (RQF) KABUPATEN FAKFAK - Rumatumia, Kalsumi; Abdillah M, Fardan (Transformasi : Jurnal Kepemimpinan & Pendidikan Islam, 2024)
This research aims to (1) Analyze the effectiveness of implementing the wafa method and habituation of tahsin at the Fakfak Qur'an House (2) Analyze the ability of Tahfidz al-Qur'an of OAP Santri before and after implementing the wafa method at the Fakfak Qur'an House (3) Analyze supporting and inhibiting factors of the wafa method and the habit of tahsin in the Qur'an House. This research uses a quantitative approach with an ex post facto type of research. Operational definition of the application of the wafa method as the independent variable (X1) and Tahsin Refraction as the independent variable (X2) Santri's Tahfidz Qur'an ability as the dependent variable (Y). The population in this study was 205 students in the even semester of 2021/2022 and then became 108 students in 2023/2024. The sample taken was 30 students with a sampling method using purposive sampling. The research instruments used in this research were documentation forms and observation guidelines. The processing and analysis techniques used are descriptive statistical analysis and inferential statistical analysis.